2005
DOI: 10.1080/09297040590951550
|View full text |Cite
|
Sign up to set email alerts
|

Finger gnosia: a predictor of numerical abilities in children?

Abstract: This paper aimed to test the specificity of predicting power of finger gnosia on later numerical abilities in school-age children and to contribute to the understanding of this effect. Forty-one children were tested in the beginning of Grade 1 on finger gnosia, left-right orientation (another sign of the Gerstmann "syndrome"), and global development. Fifteen months later, numerical and reading abilities were assessed. Analyses of the results indicated that, contrary to the general measures of cognitive develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
192
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(212 citation statements)
references
References 34 publications
12
192
0
8
Order By: Relevance
“…In addition, performance on finger discrimination tasks at 5 years of age was shown to be a good predictor of arithmetic abilities at 6 and 8 years of age (Fayol, Barrouillet, & Marinthe, 1998;Marinthe, Fayol, & Barrouillet, 2001). This finding was replicated by Noël (2005) and extended by Gracia-Bafalluy and Noël (2008), who observed that 8 weeks of finger gnosis training could improve three numerical abilities (i.e., subitizing, finger configuration naming, and ordinality judgment) in a group of first graders (but see Fischer, 2010).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…In addition, performance on finger discrimination tasks at 5 years of age was shown to be a good predictor of arithmetic abilities at 6 and 8 years of age (Fayol, Barrouillet, & Marinthe, 1998;Marinthe, Fayol, & Barrouillet, 2001). This finding was replicated by Noël (2005) and extended by Gracia-Bafalluy and Noël (2008), who observed that 8 weeks of finger gnosis training could improve three numerical abilities (i.e., subitizing, finger configuration naming, and ordinality judgment) in a group of first graders (but see Fischer, 2010).…”
supporting
confidence: 54%
“…Because learning basic arithmetic abilities is often very demanding for children's working memory, one may wonder whether training the finger-counting behavior of blind children could improve their numerical abilities (see Gracia-Bafalluy & Noël, 2008, for similar results with sighted children). Moreover, because finger discrimination appeared to be a good predictor of sighted children's arithmetic abilities (Fayol et al, 1998;Marinthe et al, 2001;Noël, 2005), it could be interesting to test whether working memory capacity might be a good predictor of blind children's arithmetic abilities. In our experiment, the first battery was designed to determine whether both groups of children had the level of performance required to undertake the counting tasks of the second test battery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The better a child understands a partition as a representation of a number, the better developed is that child's later understanding of numerical structures (Thomas et al 2002) and arithmetical skills (Hunting 2003). The more competent a child is with regard to the use of fingers in both counting and early arithmetic, skills that can be taught effectively (Gracia-Bafalluy and Noël 2008), the more competent that child is in later years (Fayol et al 1998;Jordan et al 1992;Noël 2005). Significantly, the use of finger strategies increases as socio-economic status increases, justifying targeted interventions Levine et al 1992 …”
Section: An Understanding Of Different Representations Of Numbermentioning
confidence: 99%
“…However, the developmental trajectory of these measures is still unclear. Given that some studies identified finger awareness (finger gnosia) as a significant predictor of arithmetic performance in young children (Gracia-Bafalluy & Noël, 2008;Noël, 2005;Reeve & Humberstone, 2011) we set out to determine more precisely the age at which German preschool children first reliably consider numbers as being spatially distributed from left-to-right, how they do so with their fingers compared to other objects, and whether a leftto-right preference is continuous across age groups. We also asked whether possible trends in spatial preferences would be systematically related to number knowledge.…”
Section: Introductionmentioning
confidence: 99%